EFFECT OF PROBIOTICS ADDED MOLASSES IN FEED ON GROWTH AND SURVIVAL OF MILKFISH (Chanos chanos) - Wakka, Fahad Bin Muhammad Nur; Ilmiah, Ilmiah; Hamdillah, Andi (Jurnal Perikanan Unram, 2025)
Chanos chanos is classified as a type of cultured fish with great economic value because it plays an important role in meeting the nutritional needs of the community and contributes in improving the welfare of life. Giving probiotics is one way that can be used to overcome environmental pollution. Probiotics themselves are living microorganisms that function to maintain the stability of the digestive system in the intestine. Molasses acts as a source of nutrients for probiotic bacteria and is expected to support the increase in the effectiveness of its population as bioremediation agents can be more optimal. This study aims to evaluate the effect of the addition of probiotics combined with molasses in feed on the growth and survival rate of milkfish (Chanos chanos). This research was conducted from October 10 to December 7, 2024 at Tadang Palie, Kec. Cempa. Pinrang Regency, South Sulawesi with a duration of 60 days. This research was conducted using a completely randomized design (CRD), which involved four different treatments and each treatment was repeated three times. The results showed that the effect of probiotics added to molasses in feed had a significant effect on the growth of absolute weight, specific, absolute length of milkfish. For absolute weight growth, the highest value was in treatment B (7.42 grams), the highest value of specific weight was in treatment B (9.86), the highest value of absolute length was in treatment B (9.4 cm), while survival and FCR had no significant effect on milkfish. The highest survival rate was found in treatment A (87%), and the best FCR value in treatment B (3.08).